PENINGKATAN KEMAMPUAN HAFALAN MATERI AL-QUR’AN HADITS MELALUI MODEL SAVI PADA SISWA KELAS VIII MTsN 1 MEULABOH ACEH BARAT - Daswati, Daswati (Tarbawi, 2019)
The purpose of this study is to analyze the increase in the ability to memorize the Qur'an Hadith through the SAVI learning model. This study uses classroom action research conducted in two cycles consisting of three stages, namely: design (planning), action (implementation) and reflection. The target of this study was class VIII students at State Madrasah Tsanawiyah 1 Meulaboh, West Aceh. The research subjects in this study were 30 students who took part in the Al-Hadith study. The research instrument used the Lesson Plans, observation sheets, interview sheets, student activity sheets, and non-test assessment sheets. The results showed that students' learning completeness during the pre-cycle of student mastery learning still reached 30%. While in the first cycle students 'learning completeness reached 43.33%, in the second cycle students' learning completeness reached 66.67%. So the classical increase of the pre-cycle conducted by the teacher and the second cycle conducted by the researcher was 36.67%. Keywords: Memorizing al-Qur'an Hadith, SAVI Learning Model